Book Reviews (Journal of Finance, 1986)
Book reviewed in this article: Recent Advances in Corporate Finance . Edited by EDWARD ALTMAN and MARTI SUBRAHMANYAM. Investments . By NANCY L. JACOB and R. RICHARDSON PETTIT. An Introduction to Financial Management . By GLENN V. HENDERSON, JR., GARY L. TRENNEPOHL, and JAMES E. WERT.